PERAN SISTEM FlBRINOL1S1S PADA BERBAGAI PROSES FISIOLOGIS DAN PATOLOGIS - Gde Budhiarta, Anak Agung (journal of internal medicine, 2012)
Plasminogen can be converted to plasmin either by t-PA or u-PA. A dual role for these pathways is now well established where t-PA is involved in fibrin homeostasis and u-PA is primarily involved in cell migration and tissue remodelling. Using this mechanism thrombolytic terapy of myocardial infarction and some other thromboembolic diseases have been introduced. Thrombolytic therapy could be improved by earlier and accelerated treatment, the used of plasminogen activator with increased thrombolytic potency such as reteplase, tenetecplase and staphylokinase and the use of more specific and potent anticoagulant and antiplatelet agents. Increased activity of matrix metalloproteinases (MMPs) has been implicated in numerous disease processes, including tumor growth and metastases, arthritis, and periodontal disease. It is now becoming increasingly clear that extracelluler matrix degradation by M M Ps is also involved in the pathogenesis of cardiovascular disease, including atherosclerosis, restenosis, dilated cardiomyapathi,and myocardial infarction. Administration of synthetic MMP inhibitor in experimental animal models of; these cardiovascular disease significantly inhibits the progression of respectivelyatherosclerotic lesion formation, neointima formation, left ventricular remodeling, pump dysfunction, and infarc healing.
Keywords: Plasminogen, t-PA, u-PA, PAI-1, matrix metalloproteinase